COLLEGE MONEY PAYMENT SYSTEM IN LPK WIDYA BHAKTI THANIA APPLICATIONS USING BORLAND DELPHI - Andi Herawati; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2002)
Tuition payment system in particular has a very important role towards the process ofteaching and learning activities at an educational institution. At LPK Widya BhaktiTania information presented tuition payments are still done manually so that deliverybecomes ineffective.To the writer tries to give a draft application to support the tuition payment system soas not to be done manually so it can improve work efficiency and better servic e.